Growing Black Holes: Accretion in a Cosmological Context Proceedings of the MPA/ESO/MPE/USM Joint Astronomy Conference Held at Garching, Germany, 21-25 June 2004 - Merloni, Andrea.; Merloni, Andrea.; Nayakshin, Sergei V.; Nayakshin, Sergei V.; Sunyaev, Rashid A.; Sunyaev, Rashid A. (ESO Astrophysics Symposia, European Southern Observatory,, 2005)
Supermassive black holes are now believed to play an important role in the evolution of the Universe. Every respectable galaxy hosts in its center a black hole that appears to regulate the growth of the galaxy itself. In this book, leading experts in the field review the most recent theoretical and observational results on the following topics: * formation and growth of the first black holes in the Universe and their role in the formation and evolution of galaxies * the physics of black-hole accretion and the production of relativistic jets * binary black-hole mergers and gravitational radiation. Theoretical work is supplemented by the most recent exciting results from space and ground based observatories. This volume is useful research and reference tool for the entire astrophysical community.